2010
DOI: 10.1038/modpathol.2009.177
|View full text |Cite
|
Sign up to set email alerts
|

Classifying ambiguous melanocytic lesions with FISH and correlation with clinical long-term follow up

Abstract: Recently, initial studies describing the use of multicolor fluorescence in situ hybridization (FISH) for classifying melanocytic skin lesions have been published demonstrating a high sensitivity and specificity in discriminating melanomas from nevi. However, the majority of these studies included neither histologically ambiguous lesions nor a clinical long-term follow up. This study was undertaken to validate a special multicolor FISH test in histologically ambiguous melanocytic skin lesions with known clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 22 publications
(27 reference statements)
7
89
2
Order By: Relevance
“…diagnosis of melanoma, 5,6 but is of limited utility in the assessment of histologically ambiguous melanocytic skin tumors. 12 Although the aCGH profiles correlated well with the morphological features of MLN, the correlation with FISH was poorer. The higher sensitivity of aCGH is explained by the fact that the FISH test only evaluates four genomic loci for gains and losses, in contrast to aCGH, which surveys the entire genome (Figure 2c).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…diagnosis of melanoma, 5,6 but is of limited utility in the assessment of histologically ambiguous melanocytic skin tumors. 12 Although the aCGH profiles correlated well with the morphological features of MLN, the correlation with FISH was poorer. The higher sensitivity of aCGH is explained by the fact that the FISH test only evaluates four genomic loci for gains and losses, in contrast to aCGH, which surveys the entire genome (Figure 2c).…”
Section: Discussionmentioning
confidence: 89%
“…5,12 The 5-mmthick sections were obtained from formalin-fixed paraffin-embedded tissue and mounted on SuperFrost Plus positively charged slides. The slides were baked overnight at 56 1C, deparaffinized in xylene, and dehydrated in ethanol.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…The sensitivity and specificity of the FISH method varies dramatically among existing reports with the lesion subtype, the probe set used, the number of observers, and the cutoff thresholds used. Various authors have reported a FISH sensitivity ranging from 43% to 94% and a specificity ranging from 60% to 98% 24, 25, 26, 27, 28. The original 4‐probe FISH assay targeting 6p25 (RREB1), 6q23 (MYB), Cep6 (centromere 6), and 11q13 (CCND1) was reported to discriminate between histologically unequivocal melanomas and benign nevi with a sensitivity of 86.7% and a specificity of 95.4% 24.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic utility of FISH is controversial in the setting of such ambiguous melanocytic lesions, where the overall reported sensitivity lies between 43 and 100% and the specificity between 33 and 83% using clinical behavior or expert histopathologic review as the gold standard. 6,[16][17][18][19] Of note, within spitzoid tumors, FISH testing has a low sensitivity in detecting spitzoid melanoma around 70%. Thus, to improve on the diagnostic sensitivity and specificity and to overcome the limitations imposed by tetraploidy, probes for 9p21, a region homozygously deleted in a subset of spitzoid melanomas, and for 8q24, the gain of which is associated with poorer outcome, were integrated into the standard FISH panel to increase the diagnostic sensitivity and specificity of the assay and add prognostic relevance.…”
mentioning
confidence: 99%